2010
DOI: 10.1055/s-0030-1268707
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Assisted Reproductive Technology on the Association between First-Trimester Pregnancy-Associated Plasma Protein A and Human Chorionic Gonadotropin and Adverse Pregnancy Outcomes

Abstract: We evaluated the impact of assisted reproductive technology (ART) on the association between first-trimester pregnancy-associated plasma protein A (PAPP-A) and human chorionic gonadotropin (β-hCG) and adverse pregnancy outcomes. PAPP-A and β-hCG levels were obtained between 11 and 13 (6)/ (7) weeks' gestation and converted to multiples of the median (MoM). MoM < 5th percentile was defined as low PAPP-A or β-hCG and those > 90th percentile as high. Adverse outcomes included small-for-gestational-age (SGA) infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Of those, all considered IVF, 15 considered ICSI, and five reported data concerning IVF/ICSI together . In one case, the type of ART was not specified . Anckaert et al reported data for all type of infertility but also separately for male infertility and female/unexplained infertility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those, all considered IVF, 15 considered ICSI, and five reported data concerning IVF/ICSI together . In one case, the type of ART was not specified . Anckaert et al reported data for all type of infertility but also separately for male infertility and female/unexplained infertility.…”
Section: Resultsmentioning
confidence: 99%
“…The following potential biases in the methodology of the studies included in the review were evaluated: different protocols of ART, characteristics and size of the population, ultrasound and laboratory methodology, large interval of study (from 2001 to 2016) with different correction factors and statistical approaches used for conversion of the measured raw values of free β ‐hCG and PAPP‐A to MoMs. Main characteristics of considered study are provided in Table …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, PAPP-A levels have been associated to a higher risk of small for gestational age (SGA, <10 th percentile of weight) (42, 43) and are directly correlated with insulin-like growth factor (IGF) bioavailability. The IGF system plays an important role in the communication between the embryo and the endometrium, with IGF-2 likely stimulating implantation and invasion (28).…”
Section: Potential Etiologiesmentioning
confidence: 99%
“…However, Amor et al (2009) found that PAPP-A levels were reduced in ART pregnancies with or without pregnancy complications (e.g., preeclampsia or low birth weight). In other study by Zhong et al (2010), ART pregnancies with low PAPP-A level values were at higher risk for small-for-gestational-age infants or preterm delivery less than 32 weeks of gestation when compared with spontaneous pregnancies with low PAPP-A values. Recent studies have suggested that vanishing twin might have the impact on serum marker level alterations.…”
Section: Possible Explanations For Altered Serum Marker Levels In Artmentioning
confidence: 70%